The nanotechnology among US: are metal and metal oxides nanoparticles a nano or mega risk for soil microbial communities? - Parada, J. (2018)
Metal nanoparticles and metal oxides nanoparticles (MNPs/MONPs) have been widely included in a great diversity of products and industrial applications and they are already a part of our everyday life. According to estimation studies, their production is expected to increase exponentially in the next few years. Consequently, soil has been suggested as the main sink of MNPs/MONPs once they are deliberately or accidentally released into the environment. The potential negative perturbations that may result on soil microbial communities and ecological processes are resulting in concerns. Several nano-toxicological studies of MNPs/MONPs, reported so far, have focused on aquatic organisms, animals, and soil invertebrates. However, during recent years, the studies have been oriented to understand the effects of MNPs/MONPs on microbial communities and their interaction with soil components. The studies have suggested that MNPs/MONPs are one of the most toxic type to soil biota, amongst different types of nanomaterials. This may threaten soil health and fertility, since microbial communities are known to support important biological processes and ecosystem services such as the nutrient cycling, whereby their protection against the environmental pollution is imperative. Therefore, in this review we summarize the actual knowledge available from the last five years (2013?2018) and gaps about the potential negative, positive or neutral effects produced on soil by different classes of MNPs/MONPs. A particular emphasis has been placed on the associated soil microorganisms and biological processes. Finally, perspectives about future research are discussed.